Analisis Aliran Daya Pembangkit Hybrid (Photovoltaic/Diesel) Pada Menara Mercusuar Di Pulau Pandang - ., Rimbawati; Mahendra, Yusril Ihza; Riandra, Juli; Harahap, Partaonan (Rekayasa Material, Manufaktur dan Energi, 2023)
Study of power flow analysis to obtain information about the flow of power or voltage in an electric power system. As time goes by and the number of tourists on Pandang Island, especially in the development and change sector, will also increase, the amount of burden incurred will also increase, so that a good initial design is no longer suitable for the current load. For this reason, it is necessary to analyze the power flow in order to determine the condition of the electric power system. The benefits of this research are also for planning evaluation if there will be additional burden innovations. In this study, ETAP Power Station 19.0 software was used using Newton Raphson for power flow simulation. The results obtained in the Etap simulation are 37% generating load with a total active power of 10.35 KW, reactive power of 6.85 Kvar, and apparent power of 12.42 KVA. This research also increases the load by 4,800 watts, where the photovoltaic generator must increase the photovoltaic capacity from the previous 10.26 kw to 13.29 kw, therefore solar cell panels will be added as many as 8 panels.